2014
DOI: 10.12968/bjon.2014.23.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Nursing documentation of inpatient care in eastern Ghana

Abstract: The standard of nursing care documentation is not on a par with that in developed countries, partly owing to a lack of guidelines, as well as a persistent shortage of nurses and the limited use of nursing care records. It is recommended that nursing stakeholders use a multidisciplinary approach to develop policies/guidelines on nursing care documentation and provide training opportunities for nurses on effective documentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
49
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 19 publications
11
49
4
2
Order By: Relevance
“…Attaining standard training on nursing documentation was positively associated. This finding is comparable with the finding of the study conducted in Ghana (18), Uganda (5) and Gondar (1).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Attaining standard training on nursing documentation was positively associated. This finding is comparable with the finding of the study conducted in Ghana (18), Uganda (5) and Gondar (1).…”
Section: Discussionsupporting
confidence: 91%
“…Ghana (18) and Jimma (17). The possible reason for this variation might be the tool utilized to determine the practice level of documentation (2, 17) self-administered questionnaire was used in those studies but medical record review for this study and this might be the fact that self-reported documentation practice may be overestimated due to social desirability bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with findings in some of the reviewed literature, it was found that even though over two thirds of the staff demonstrated knowledge of standard policy protocols, similar to findings by [7,12,26,27], there was an incommensurate application of the knowledge in real practice of their duties.…”
Section: Discussionsupporting
confidence: 78%
“…A study conducted in ten hospitals on point prevalence of HAIs in Ghana found that out of the 2,107 inpatients surveyed, 184 HAIs were found among 172 patients, representing an overall prevalence of 8.2% with the most common HAIs being surgical site infections [3]. Similar studies on Ghana [4][5][6][7][8][9] and elsewhere [10][11] have alluded to high prevalence of HAIs related to wound infections be they septic or surgical (also referred to as aseptic wounds in this paper).…”
Section: Introductionmentioning
confidence: 89%